2012
DOI: 10.1016/j.cub.2011.12.010
|View full text |Cite
|
Sign up to set email alerts
|

Actin Filaments as Tension Sensors

Abstract: The field of mechanobiology has witnessed an explosive growth over the past several years as interest has greatly increased in understanding how mechanical forces are transduced by cells and how cells migrate, adhere and generate traction. Actin, a highly abundant and anomalously conserved protein, plays a large role in forming the dynamic cytoskeleton that is so essential for cell form, motility and mechanosensitivity. While the actin filament (F-actin) has been viewed as dynamic in terms of polymerization an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
138
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 158 publications
(145 citation statements)
references
References 50 publications
7
138
0
Order By: Relevance
“…1B). A previous observation using the compression of actin filaments between two thin mica plates observed a stiffening of these filaments under force (Greene et al, 2009), which appears to be the same phenomenon as the rigidification of F-actin observed in thin ice (Galkin et al, 2012). In order to reduce structural heterogeneity within the actin filament to achieve the highest possible resolution we used blotting conditions (see Materials and Methods) which yielded very thin ice (Fig.…”
Section: Resultssupporting
confidence: 59%
See 1 more Smart Citation
“…1B). A previous observation using the compression of actin filaments between two thin mica plates observed a stiffening of these filaments under force (Greene et al, 2009), which appears to be the same phenomenon as the rigidification of F-actin observed in thin ice (Galkin et al, 2012). In order to reduce structural heterogeneity within the actin filament to achieve the highest possible resolution we used blotting conditions (see Materials and Methods) which yielded very thin ice (Fig.…”
Section: Resultssupporting
confidence: 59%
“…We recently suggested that the structural state of actin filaments can be modulated by applied forces (Galkin et al, 2012). Samples are prepared for cryo-EM by blotting a drop applied to a grid so that only a thin film remains, which is then rapidly frozen.…”
Section: Resultsmentioning
confidence: 99%
“…The link between the mechanics of actin filaments, ADF/cofilin, and severing was further investigated using optical tweezers to stretch actin filaments, revealing that stretched actin filaments are resistant to ADF/cofilin binding/severing (95,117). This observation is in line with the idea that actin filaments may act as tension sensors to modulate their own dynamics.…”
Section: Adf/cofilin-induced Disassemblysupporting
confidence: 64%
“…Our understanding of actin SFs has evolved from a static cable of actin to a flexible, dynamic structure that functions as a tension sensor [27]. Actin SFs anchor at sites of integrin-based FAs forming a complex interface between SFs and FAs.…”
Section: Regulation Of Force By Stress Fibersmentioning
confidence: 99%